Uniformification of Urban Spaces: The Midyat Case - Sel, Berna Dikcinar; Gul, Ayfer Yazgan (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2009)
Urban spaces today have become commodities in production, circulation and consumption. While globalization accentuates the commodification of urban spaces on an international scale, cities, on the other hand, have become areas where investments of both local and global capital concentrate. In this process, cities in countries located in different geographies compete with one another, and urban spaces are becoming much more alike. Even cities that have fallen outside global competition are influenced by this transformation, as they go through the processes of assimilation and uniformification in their wish to resemble cities in a geography and with a culture other than their own. Midyat is a city with a multi-cultural structure containing religious and ethnic diversities, and thus it is referred to as the city of faiths and tongues. Since the 1980s, the terror acts in the region and the migration that followed have greatly affected the social structure of the settlement. As Assyrians and Yazidis, important cultural and social contributors in Midyat, left the region, Kurds fleeing from settlements disturbed by the acts of terrorism or who were part of the mandatory migration settled in the vacated areas. The changing population structure of Midyat has also altered the spatial characteristics of the city. Urban spaces containing the traces of the cultural diversity of the city are being replaced by structures resembling the building developments in large cities, and the city has been undergoing a process of uniformification with other cities. This article evaluates the process of uniformification experienced in Turkish cities through the example of the Midyat case.
Keywords: Assimilation-uniformification; migration; urbanization; culture-identity; planning; Architecture